Deferoxamine Inhibition of Cr(V)-Mediated Radical Generation and Deoxyguanine Hydroxylation: ESR and HPLC Evidence - X. Shi; P. M. Gannett; N. S. Dalal (The National Institute for Occupational Safety and Health (NIOSH), 1992)
"Chromates are known to induce tumors (1, 2), mutations (3), and DNA damage (4-6). However, the underlying biochemical mechanism(s) is (are) not fully understood (6). Recent studies have indicated that hydroxyl (·OH) radical may play an important role (7-11). The mechanistic studies of Cr(Vl)-related ·OH radical generation in biochemical systems have shown the reaction of a Cr(V) species with hydrogen peroxide (H20 2 } through a Fenton-like mechanism to be one of the important steps (9-11): Cr(V) + H20 2 - Cr(VI) + ·OH + OH-. (1)In biological systems the Cr(V) species are generated via the reduction of Cr(VI) by a variety of components, such as microsomes (12), mitochondria (13), mitochondrial electron transfer complexes (14), and at least three flavoenzymes (glutathione reductase (GSSG-R),3 lipoyl dehydrogenase, and ferredoxin-NADP+ oxidoreductase) (9, 15, 16). In the case of flavoenzymes, Cr(V) formation is accompanied by the reduction of molecular oxygen ( 0 2 ) to H20 2 • The Cr(V) species then reduces H20 2 to generate •OH radicals and Cr(VI) (16).To understarid the mechanism by which Cr(V}-generated ·OH radicals cause cytotoxicity, Aiyar et al. (8) investigated the reaction of Cr(VI) and H20 2 to generate ·OH radical and its reaction with 2'-deoxyguanine (dG) to form 8-hydroxy-2'-deoxyguanine (8-0HdG}:"